Simple Tibetan Buddhism : Annellen M. Simpkins Ph. D. - Simpkins, C.Alexander.; Simpkins, Annellen (North Clarendon : Tuttle Publishing, 2017)
What is Tantra' Tantra techniques are very ancient and some form is found in many ancient cultures. The Sanskrit word tantra implies continuation, weaving together, but there is no real single definition. Tantra includes many sets of techniques, usually action-oriented, to weave together mind and body. Simple Tibetan Buddhism: A Guide to Tantric Living offers: -a concise introduction to the unique history and traditions of Tibetan Buddhism -a clear explanation of how Tibetan Buddhism differs from Zen and other forms of Buddhism'and why it's so popular today -simple exercises incorporating Tibetan Buddhist practices'incluing visualizations, deity yoga, mandalas, mantras, and the esoteric yet effective tantric methods.
11: Meditating the Tantric Way12: Entering Through Art; 13: Martial Arts: Enlightened Patterns; 14: Dialogue with Science; 15: Wisdom Through Love; 16:Transformation Through the Great Symbol; Conclusion; Bibliography.
Print version record.
Keywords: Buddhism -- China -- Tibet Autonomous Region; Religious life -- Buddhism; ART -- Subjects & Themes -- Religious; Buddhism; Religious life -- Buddhism; China -- Tibet Autonomous Region; Electronic books